Selecting Hormonal Contraceptives in Women Taking Antiepileptic Drugs : Review of Literature and Practical Recommendations - Hendra Permana; Restu Susanti; Syamel Muhammad (Universitas Andalas, 2020)
Contraception is a very important issue in women with epilepsy, since very broad questions taken in applying it to prevent unplanned pregnancy. The choice of contraceptive methods must be related to how the mechanism of action of antiepileptic drugs (AEDs), the contraceptive itself, and both interactions. Hormonal contraception can induce metabolism of AEDs and lead to increasing of seizure frequency, and in the other hand AEDs may decrease the blood levels of hormonal contraception. Therefore, physician must consider the type of contraception being used before prescribing AEDs. Additionally, they should emphasize the interaction between them in counseling, to assure that women with epilepsy have time to decide which type will be best use for them. This challenging matter needs better recommendation for practice, both neurologist and gynecologist.Keywords: antiepileptic drug, contraception, women with epilepsy